Jejak Spiritualitas Lokal: Banjari sebagai Agen Moderasi Beragama di Desa Maguan - Nur Handayani, Elsa; Ria Retnasih, Nora; Khilmi Muzakki, Dzul (LP2M IAIN Sultan Amai Gorontalo, 2024)
Abstract:This article discusses the role of banjari as an agent of religious moderation in Maguan Village by emphasizing the importance of religious moderation amidst the diversity of society. Through the ABCD approach, community service emphasizes local potential in community development, with initial observations to understand attitudes of religious moderation. Banjari training by KKM group 60 students at UIN Maulana Malik Ibrahim Malang aims to strengthen the values of moderation among the children of Maguan Village. The use of Tanpo Waton poetry as a means of conveying a universal message highlights the importance of living in harmony with human diversity. Banjari training has a positive impact by introducing spiritual values, providing a platform for creativity, creating useful time, and getting positive support from the community. The article concludes that engaging arts and religious activities in moderation can be an effective tool for building understanding, tolerance, and harmony in multicultural societies.